Ruskin and Gender - Birch, Dinah. author. aut Link
XIV, 211 p. 4 illus.
Keywords: For many years Ruskin has seemed, at best, a conservative thinker on gender roles. At worst, his lecture On Queens' Gardens from Sesame and Lilies was read as a locus classicus of Victorian patriarchal oppression. These essays challenge such assumptions, presenting a wide-ranging revaluation of Ruskin's place in relation to gender, and offering new perspectives on continuing debates on issues of gender - in the Victorian period, and in our own.